Lip filling associated with subcision in a patient with cleft lip and palate (Research, Society and Development, 2022)
To describe a case of lip filling associated with subcision of the ligaments of the orbicularis oris muscle and the superficial musculoaponeurotic system (SMAS) of a patient with cleft lip and palate. Case details: A 42-year-old woman was seen at a dental clinic specializing in orofacial harmonization (Instituto Erlacher) with a complaint of lip asymmetry. She reported being born with cleft lip and palate and being submitted to surgical intervention by an oral and maxillofacial surgeon. After clinical evaluation and planning, a subcision technique was performed prior to lip filling with hyaluronic acid, with the objective of maintaining good tissue integration of the product, avoiding its migration to other regions, and reducing local resistance due to scar fibrosis. Final considerations: This study revealed that even though it is not a definitive procedure, which requires periodic maintenance, the minimally invasive treatment with the injection of hyaluronic acid through the subcision technique is capable of immediately correcting the lip asymmetry of patients with cleft lip and palate. looking for the procedure.